Characterization of pathogenic Aeromonas veronii bv. veronii associated with ulcerative syndrome from Chinese longsnout catfish (Leiocassis longirostris Günther) - Cai,Shuang-Hu (2012)
273 bacterial strains were isolated from 20 Chinese longsnout catfish samples. The biochemical characteristics of all strains conformed to the species description of Aeromonas veronii bv. veronii on the basis of Vitek GNI+ card. Furthermore, 16S rDNA, gyrB and rpoD sequences of the representative strain PY50 were sequenced and showed high similarity with A. veronii bv. veronii in Genbank. Antibiotic-resistance of the representative strain PY50 was assessed by the Kirby-Bauer disk diffusion method, and the results showed it was susceptible and moderately susceptible to 13 and 4 of the 21 antimicrobial agents tested. Extracellular products of strain PY50 contained gelatinase, lecithinase, elastase, most of lipase and lipopolysaccharide. Virulence of strain PY50 and extracellular products to Chinese longsnout catfish were also tested, and LD50 were about 3.47×10(4) CFU per fish and 11.22 μg per fish in intraperitoneal injection respectively. This is the first report that A. veronii bv. veronii was the pathogenic agent of ulcerative syndrome in Chinese longsnout catfish.